If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 17 = 86 Reorder the terms: 17 + -4x = 86 Solving 17 + -4x = 86 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + -4x = 86 + -17 Combine like terms: 17 + -17 = 0 0 + -4x = 86 + -17 -4x = 86 + -17 Combine like terms: 86 + -17 = 69 -4x = 69 Divide each side by '-4'. x = -17.25 Simplifying x = -17.25
| 4p(p)+8p=0 | | 10x-30=-80 | | (2b+1)(2b+1)=25 | | -5x+6y=69 | | 15x+17=-73 | | -6x-63=-75 | | -6-63=-75 | | x^3-6x-9=0 | | 3(x^2)+32x+45= | | x(x)-x-20=0 | | 30(x^2)+37x+10= | | 16=4(x-5)2 | | x(x)+12x-13=0 | | 8xy-120(x^2)(y^4)= | | x(x)-8x+12=0 | | (t+2)(t+2)=4 | | (t+2)2=4 | | 28-5x=4x+8 | | y=12x^2+203x+7 | | (6x+5)(4x+8)= | | 4x^2+6x+7=0 | | 3(n+1)=2(n+4) | | (-6x^2+10x+8)+(-8x^2+2x+6)= | | x^2+3x-x-3=0 | | 4x^2+7x-57= | | x^2-3x-x-3=0 | | -4(2.5x+8.7)=(1.4-9.2x)(6) | | 5x^2+9x-72= | | 9h=49 | | 7-5x-5-7x=5 | | 3-0.4k=3 | | s^3-3s^2-3=0 |